Heart Valve Biomechanics: The Frontiers of Modeling Modalities and the Expansive Capabilities of Ex Vivo Heart Simulation - Park, Matthew H.; Zhu, Yuanjia; Imbrie-Moore, Annabel M.; Wang, Hanjay; Marin-Cuartas, Mateo; Paulsen, Michael J.; Woo, Y. Joseph (Frontiers in Cardiovascular Medicine, 2021)
The field of heart valve biomechanics is a rapidly expanding, highly clinically relevant area of research. While most valvular pathologies are rooted in biomechanical changes, the technologies for studying these pathologies and identifying treatments have largely been limited. Nonetheless, significant advancements are underway to better understand the biomechanics of heart valves, pathologies, and interventional therapeutics, and these advancements have largely been driven by crucial in silico, in vitro, and in vivo modeling technologies. These modalities represent cutting-edge abilities for generating novel insights regarding native, disease, and repair physiologies, and each has unique advantages and limitations for advancing study in this field. In particular, novel in vitro modeling technologies represent an especially promising class of translatable research that leverages the advantages from both in silico and in vivo modeling to provide deep quantitative and qualitative insights on valvular biomechanics. The frontiers of this work are being discovered by innovative research groups that have used creative, interdisciplinary approaches towards recapitulating in vivo physiology, changing the landscape of clinical understanding and practice for cardiovascular surgery and medicine.